Skin autofluorescence is increased in patients with carotid artery stenosis and peripheral artery disease - Noordzij, Marjon J. (Springer Netherlands, 2011)
Advanced glycation end products (AGEs) have a pivotal role in atherosclerosis. We evaluated skin autofluorescence (SAF), a non-invasive measurement of tissue AGE accumulation, in patients with carotid artery stenosis with and without coexisting peripheral artery occlusive disease (PAOD). SAF was measured using the AGE Reader™ in 56 patients with carotid artery stenosis and in 56 age- and sex-matched healthy controls without diabetes, renal dysfunction or known atherosclerotic disease. SAF was higher in patients with carotid artery stenosis compared to the control group: mean 2.81 versus 2.46 (P = 0.002), but especially in the younger age group of 50–60 years old: mean 2.82 versus 1.94 (P = 0.000). Patients with carotid artery stenosis and PAOD proved to have an even higher SAF than patients with carotid artery stenosis only: mean 3.28 versus 2.66 (P = 0.003). Backward linear regression analysis showed that age, smoking, diabetes mellitus, renal function and the presence of PAOD were the determinants of SAF, but carotid artery stenosis was not. SAF is increased in patients with carotid artery stenosis and PAOD. The univariate and multivariate associations of SAF with age, smoking, diabetes, renal insufficiency and PAOD suggest that increased SAF can be seen as an indicator of widespread atherosclerosis.